Digitally signed electronic certificate for workshop / Azinuddin Baharum - Baharum, Azinuddin (2017)
Entering into the era of advancement in Information Technology, publishing qualification certificate in electronic form going forward. E-Certificate helps eliminate many problems that is associated with physical printed certificate such costs, management, and forgery problem. Even though implementation of such E-Certificate have been implemented around the globe, it has not been implemented for workshops in UiTM. User who owes an E-Certificate is able to retrieve from a web page and can be printed out. In order to handle the integrity issue, each certificate must be digitally signed by a signatory, and equivalent to hand signature. Digital Signature was encrypted by RSA Algorithm, a very powerful asymmetrical encryption. The system consist of a central database and organized into web page application which can be accessed by system admin, certificate user, and employer. In order to maintain the integrity of the E-Certificate, employers are allowed to verify the certificate in a specially made webpage to authenticate it. Web page application was programmed by Java Enterprise Edition (J2EE). Signatory however use a special Digital Signature Application which store the secret private key. The application was programmed by JAVA FX. The system was developed stage by stage as it is consist of many small components to form a large system. Therefore tests can be conducted as you develop the system. From tests, it was observed that all functions perfectly, accurately, and swiftly, indicating the advantages of an E-Certificate system.